Mapping of the air pollution dispersion in the Klang Valley using remote sensing and GIS techniques / Suharti Ismail - Ismail, Suharti (2007)
Degradation of air quality in Malaysia recently is very concerning and getting worse day by day. Therefore, this study intent to map the air pollution dispersion by acquiring aerosol information using remotely sensed data and then interpolate the information to produce air pollution map. Satellite sensors have been used widely in monitoring and observing the atmosphere; nowadays there are a number of sensors capable of monitoring the aerosols, atmosphere and Earth dynamical changing. Abroad studies have shown tremendous results in mapping the air pollution using remotely sensed data and GIS techniques. This research comprises of three different stages; i) data preparation and study area selection, ii) processing stage and iii) data and results analyzing. This study addressed the Klang Valley as the study area and major pollutants (SO2, NO2, O3, CO and PM10) are used in selecting the image and results validation. The software packages used are mainly Erdas Imagine (digital data processing) and ArcGIS (Kriging technique). The method used is based on radiometric comparison between two sets of image; clear and polluted. Clear image is polluted-free image and consumed as reference image while polluted image is the image considered to be contaminated by pollutant. This study investigates the aerosol contents through remotely sensed data for the polluted day. Aerosol optical thickness (AOT) is quantified to represent the amount of pollutant loading in the atmosphere thus presenting the air pollution level. Satellite imageries have to go through several methods; geometric correction, calibration and conversion to apparent reflectance image before calculating of AOT. The image is divided into 625 pixel grids and each grid produces one standard deviation. All standard deviations of the apparent reflectance image are used in formulation of AOT. Certain algorithms and equations are employed in this study. The values of AOT constituted the pollution level and Kriging technique is used to estimate the missing values and generate the air pollution map. Based on the profile result, satellite-derived AOT has proven to be in relationship with the ground data when all the pollutants are considered altogether as well as when they are considered separately. Four bands are used in quantification of AOT and each band resulted in moderately different aerosol dispersion. Therefore, AOT has proven to be a good air quality indicator. The final results are maps showing the air pollution dispersion in the atmosphere based on satellite-derived aerosol values.